NOTCH inhibition promotes bronchial stem cell renewal and epithelial barrier integrity after irradiation. (16th April 2020) - Giuranno, Lorena; Roig, Eloy M.; Wansleeben, Carolien; Berg, Annette; Groot, Arjan J.; Dubois, Ludwig; Vooijs, Marc
Abstract: Hyperactivity of the NOTCH pathway is associated with tumor growth and radiotherapy resistance in lung cancer, and NOTCH/ γ -secretase inhibitors (GSIs) are a potential therapeutic target. The therapeutic outcome, however, is often restricted by the dose-limiting toxicity of combined treatments on the surrounding healthy tissue. The NOTCH signaling pathway is also crucial for homeostasis and repair of the normal airway epithelium. The effects of NOTCH/ γ -secretase inhibition on the irradiation of normal lung epithelium are unknown and may counteract antitumor activity. Here we, therefore, investigated whether normal tissue toxicity to radiation is altered upon NOTCH pathway inhibition. We established air-liquid interface pseudostratified and polarized cultures from primary human bronchial epithelial cells and blocked NOTCH signaling alone or after irradiation with small-molecule NOTCH inhibitor/GSI. We found that the reduction in proliferation and viability of bronchial stem cells (TP63+) in response to irradiation is rescued with concomitant NOTCH inhibition. This correlated with reduced activation of the DNA damage response and accelerated repair by 24 hours and 3 days postirradiation. The increase in basal cell proliferation and viability in GSI-treated and irradiated cultures resulted in an improved epithelial barrier function. Comparable results were obtained after in vivo irradiation, where the combination of NOTCH inhibition and irradiation increased the percentage of stem cells and ciliated cells ex vivo. These encourage further use of normal patient tissue for toxicity screening of combination treatments and disclose novel interactions between NOTCH inhibition and radiotherapy and opportunities for tissue repair after radiotherapy. : Abstract :